PRINCIPLES OF JUSTICE IN LAND ACQUISITION GRANT OF COMPENSATION FOR PUBLIC INTEREST (CASE STUDY IN THE CITY highway widening Praya Central Lombok) - Zarkasih, Hery (Jurnal IUS, 2015)
Process of the implementation of compensation for land acquisition for public purposes in the town of Praya carried out under the provisions of Law No. 2 of 2012 on Land Procurement for Development for Public Interest starts from the stage of assessment, the results of the assessment became the basis of the implementation of the deliberations in the determination of damages and villages Prapen Panjisari, When viewed from perspektif justice John Rawls, then compensation in the procurement of land in the town of Praya including unfair, John Rawls suggests an element of substantive justice and procedural fairness element. Some of the obstacles in the indemnity is a dispute between the owner of the land affected by the widening of the road by the old owners. The governmentâs efforts is through deliberation to find the best solution. Keywords: Justice, Compensation, Land Acquisition